Testing of Radio Frequency Identification and Parameter Analysis Based on DOE - Lidong Wang (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The maximum read range of a Radio Frequency Identification (RFID) system depends on a number of factors. In this paper, the maximum read ranges of an RFID system with a handheld RFID reader and another RFID system with a fixed RFID reader were tested when a tag was attached to different materials. Distinguishing factors that influence the maximum read range is important. A design of experiments (DOE) method was used to understand and quantify the relative influence of three factors (the antenna number, the tagged material, and the RF interference) on the maximum read range of the RFID system with a fixed RFID reader. The influences of the three factors and their interaction effects were classified by an order of importance. The methods in this paper also apply to the study of other RFID systems and determining the relative influences of other selected factors or parameters as well as other materials.DOI:http://dx.doi.org/10.11591/ijece.v4i1.5103